The Dialectic of the Colonizer and the Colonized in Abdulrazak Qurnah’s After Death: A Postcolonial Reading - Ibrahim, Razan (Dirasat: Human and Social Sciences, 2024)
Objectives: The study aimed to explore the colonial state that the novelist Abdulrazak Qurnah exemplifies in his novel carrying the title of After Death. This state places the colonized in a halo of inferiority complex which renders him oblivious to his existence and compels the colonized to blindly imitate the colonizer in a way that negates all possible solidarity between the two parties. Methods: This study relied on the poetics of postcolonial theory. The study approaches the text as a reactionary act to the colonial practices in East Africa. Results: The study results showed that coloniality exerts strenuous efforts to keep the colonized under control and domination. The results also set an alarming observation regarding the colonizer’s plan to let the colonized derail and diverge from the path of resistance and place the colonized in a state of helplessness and succumbing to the colonizing elite dominated by an alleged mighty civilized force. Conclusions: The researcher emphasizes the need to deepen and increase research pertinent to international narratives that helped divulge the shameful past of European colonialism.